2022
DOI: 10.1111/apa.16475
|View full text |Cite
|
Sign up to set email alerts
|

An overview of reviews for preventing and treating sleep problems in infants

Abstract: Aim Parents and professionals receive conflicting recommendations about management of infant sleep problems. The aim of this umbrella review was to provide an overview of summarised research on the prevention and treatment of sleep problems in infants (0–1 year), content of the interventions and the conditions under which they are delivered. Methods The umbrella review included five systematic reviews of 24 individual studies, mainly randomised controlled trials. Searches were conducted in PsycINFO, Cochrane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…An important next step for identifying the role of predictability on child outcomes is the implementation of randomized controlled trials (RCTs) in the context of intervention research. Although not focused on predictability, prior intervention work clearly has demonstrated that changing the child's environment has the potential to change child behavior (Bick, Palmwood, Zajac, Simons, & Dozier, 2019; Dozier, Roben, Caron, Hoye, & Bernard, 2018; Drozd, Leksbø, Størksen, Wilhelmsen, & Slinning, 2022; Hwang, Chao, & Liu, 2013; Mountain, Cahill, & Thorpe, 2017). We now need to develop and evaluate interventions that increase predictability in the child's environment.…”
Section: Cross‐cutting Themes and Future Directionsmentioning
confidence: 99%
“…An important next step for identifying the role of predictability on child outcomes is the implementation of randomized controlled trials (RCTs) in the context of intervention research. Although not focused on predictability, prior intervention work clearly has demonstrated that changing the child's environment has the potential to change child behavior (Bick, Palmwood, Zajac, Simons, & Dozier, 2019; Dozier, Roben, Caron, Hoye, & Bernard, 2018; Drozd, Leksbø, Størksen, Wilhelmsen, & Slinning, 2022; Hwang, Chao, & Liu, 2013; Mountain, Cahill, & Thorpe, 2017). We now need to develop and evaluate interventions that increase predictability in the child's environment.…”
Section: Cross‐cutting Themes and Future Directionsmentioning
confidence: 99%
“…The study indicated that short fragmented sleep in early infancy did not need to predict poor development. Another paper, by Drozd et al, summarised a number of reviews on the prevention and treatment of sleep problems in infants up to 1 year of age 2 …”
Section: Not Sleeping Soundly In Early Infancy Is Not Badmentioning
confidence: 99%
“…Few parents, however, raise their concerns about their child’s sleep problems with health professionals (HPs) and many HPs have little or no formal training in pediatric sleep [ 1 ]. There are effective psychosocial and behavioral interventions [ 3 , 4 ], but their descriptions in research often lack in detail to help HPs in their implementation [ 5 ]. This may result in underidentification and undertreatment of pediatric sleep problems [ 1 ], and the endorsement and delivery of sleep assessment and treatments that are not evidence-based [ 6 ].…”
Section: Introductionmentioning
confidence: 99%